Estrategias publicitarias para el reconocimiento y visibilidad de marca de la Pymes Mundo Pura Pinta - Pazmiño Pintag, Marlon Oswaldo (2024)
This project addresses a problem for the Pymes Mundo Pura Pinta in the limited approach to advertising in digital platforms environments generating an impact on visibility and brand recognition. For this reason, it has become necessary to develop advertising strategies with the aim of providing visibility to the brand to connect with its target; for the realization of this project, the research proposal was developed with the implementation of quantitative and qualitative approaches; in addition to conducting surveys aimed at the consumer. The market analysis and the identification of the target visualized that Mundo Pura Pinta should be directed to consumers with an age range between 25 and 37 years old. Through the surveys, positive and negative factors were detected in relation to the perception of the brand, framing the management of advertising strategies in social media. The SWOT study identified opportunities for continuous improvement and the development of advertising strategies for the impact of brand recognition and visibility. Thus, this research will implement a strategic brand plan for digital platforms, establishing an advertising schedule to access greater dynamism in digital platforms, connection with consumers, automation of advertising processes, performance in target reach and project brand visibility.